CORPORATE SOCIAL RESPONSIBILITY AND FINANCIAL PERFORMANCE OF LISTED CEMENT MANUFACTURING COMPANIES IN NIGERIA - Adebowale OGUNSOLA (Malete Journal of Accounting and Finance)
The relevance of corporate social responsibility in corporate performance needs continuous reassessment for the validity or otherwise of the previous related studies. This informed the current study to empirically examine whether corporate social responsibility (CSR) has effect on financial performance of listed cement manufacturing companies in Nigeria. The study is based on ex-post facto research design using secondary data. The study population consisted of three cement manufacturing companies quoted on Nigerian Exchange Group. However, two of the three companies formed sample size based on data availability, while data for the study were extracted from the audited annual reports of the sampled cement companies. The data obtained were analyzed with the use of descriptive statistics, correlation, and regression method, and it was statistically observed that corporate social responsibility has a positive, but negligible effect on return on asset. It was also observed that the effect of corporate social responsibility on earnings per share is positive and substantial. It can be summarized that good corporate responsibility will possibly improve the financial performance of a firm. It is therefore recommended that organizations should engage in different philanthropic activities to continue to enjoy peaceful coexistence with the members of the host community. Moreover, it is expected of every corporate entity to have effective control measures in place to cushion the negative effect of its activities on the operating environment. This will, however, impact positively on the firm’s performance